AVALIAÇÃO DO CONSUMO ALIMENTAR DE ADOLESCENTES DE ESCOLAS PÚBLICAS EM SÃO LUÍS, MA - GOMES, Sinara Regina Lisboa (2017)
BACKGROUND: Adolescence is a phase of nutritional risk, in which nutritional deficiencies and excesses can negatively affect the current and future health of this population. OBJECTIVE: The objective of this study was to analyze food consumption in adolescents aged 15 to 18 years. METHODS: A cross - sectional study with a probabilistic sample of 378 adolescents enrolled in public schools in São Luís, Maranhão, Brazil. The food consumption was evaluated by two 24-hour Reminder Inquiries. Consumption of energy, macronutrients, fibers and micronutrients were compared to the values recommended by the Dietary Reference Intakes, according to age and sex. Nutrient intakes were corrected with the removal of dietary variability. RESULTS: It was verified that most of the adolescents had adequate consu mption of carbohydrates and proteins. Energy consumption was statistically significant between the sexes, with insufficient prevalence in boys and higher higher consumption among girls (p <0.001). Among the macronutrients, the lipids presented greater inadequate consumption, especially of saturated fats, which had a higher percentage of excessive consumption. Consumption of calcium, potassium, vitamins A, C and E and fiber did not reach recommendations in both sexes. Sodium intake was excessive in 60.8% mal e adolescents and 42.4% in female adolescents. CONCLUSION: It is concluded that the diet of adolescents remains deficient in vitamins and minerals and nutritional excesses, especially saturated fats and sodium, which can put this population at risk for the development of diseases. Intervention measures are necessary to reverse this framework, as well as research that analyzes their short-, medium- and long-term impacts.